Caring approaches to young, gifted music learners' education: a PRISMA scoping review - López-Íñiguez, Guadalupe; McPherson, Gary E. (Frontiers in Psychology, 2023)
This study reviews empirical research literature that deals with existing caring approaches to nurture and educate gifted children in music. The focus on the ethics of care stems from the need to expand notions of talent development in music from a purely behaviorist focus often associated with traumatic experiences, toward a perspective that addresses socio-emotional and cultural aspects of human development across the lifespan. We employed the Preferred Reporting Systems for Systematic Reviews and Meta-Analyses for Scoping Reviews method to review literature concerning caring approaches to the upbringing and education of children gifted for music. A total of 652 records dating from the 1930s and searched via both digital databases and manually in 41 relevant journals were retrieved from which 506 were examined using our inclusion criteria. A detailed analysis process allowed the authors to include 14 studies that were organized according to sampling location, methodologies, quality appraisal, and criteria-related topics. Eleven of the studies were qualitative with a majority of these employing semi-structured interviews for data collection, while the remaining meta strategy and quantitative studies typically employed questionnaires. Salient topics covered by the selected studies included: addressing inequalities in opportunity to access gifted programs; identifying socio-emotional needs of gifted (and twice-exceptional) students; offering a nurturing environment; focusing on intrinsic motivation; developing coping strategies for overall wellbeing; and cultivating healthy attitudes towards competitions through a spirit of peer collaboration and humility. These aspects were clustered into Gagné's (2021) Differentiated Model of Giftedness and Talent regarding natural abilities, environmental, intrapersonal, and developmental catalysts that are involved in nurturing talents in gifted children. Results suggest that the existing research on caring approaches to musically gifted children's learning and development are scarce and that current knowledge is based mostly on single one-off studies rather than systematic research, and on studies that examine a selection of aspects but not adopting a larger-scale theoretical framework. This review highlights the need for more systematic, multidisciplinary, and empirically robust studies on caring approaches to musically gifted children's learning and development, and for policy developments in educational settings where acceleration programs are offered for young, gifted music learners.